Changes in food-related costs during the COVID-19 pandemic among families managing food allergy - Golding, Michael A.; Lemoine-Courcelles, Cathérine; Abrams, Elissa M.; Ben-Shoshan, Moshe; Bégin, Philippe; Chan, Edmond S.; Chu, Derek K.; Gerdts, Jennifer D.; Povolo, Beatrice; Kim, Harold; Simons, Elinor; Upton, Julia; et al. (Frontiers in Allergy, 2022)
Background The COVID-19 pandemic has affected the supply, cost, and demand for certain foods, but it is not clear how these changes have affected food-allergic households. Objective To describe the changes in food-related costs that have followed COVID-19, as reported by higher- and lower-income households with a food-allergic member. Methods Between May 1-June 30, 2020, Canadian households, with at least one food-allergic member, completed an online survey on food shopping and preparation habits before and during the COVID-19 pandemic. The sample was divided into binary groups, either higher or lower than the sample median income. Data were analyzed using descriptive statistics and multiple regression. Results The sample was comprised of 102 participants (i.e., 51/ income group). The three most common food allergies amongst both groups were peanuts, tree nuts and milk. Since the start of the pandemic, both groups reported greater monthly direct grocery costs, although costs amongst the higher-income group were twice as high as the lower-income group ($212.86 vs. $98.89, respectively). Indirect food preparation costs were similarly elevated. Higher-income households with food procurement difficulties reported increased indirect shopping costs following the outbreak of COVID-19, whereas those without such difficulties reported decreased costs. Lower-income households with allergies to milk, wheat, or eggs (i.e., staple allergy) experienced a larger change in indirect food preparation costs following the outbreak of COVID-19 relative to those with other food allergies ($244.58 vs. –$20.28, respectively; p = 0.03). Conclusion Both higher and lower income households with food allergy reported greater direct food costs and indirect food preparation costs following the COVID-19. Households with staple allergy and those with difficulties finding their typical food items were particularly affected.